2021
DOI: 10.3390/jcm10173949
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity Is Related to Inflammatory Disease Activity in Juvenile Idiopathic Arthritis

Abstract: Objective: To identify factors associated with the higher proportion of fatty tissue and overweight/obesity observed in patients with juvenile idiopathic arthritis (JIA). Patients and methods: We performed a cross-sectional study of 80 JIA patients aged 4–15 years with 80 age- and sex-matched healthy controls. Body composition was assessed using dual-energy x-ray absorptiometry. The 27-joint Juvenile Arthritis Disease Activity score (JADAS27) was calculated. Two multivariate models were constructed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Based on our evaluation of various inflammatory parameters, we found a stronger association between cognitive decline and C-reactive protein than with clinical activity indexes such as JADAS27. The activity index JADAS27 is the most used in JIA [ 25 , 37 ]. Shin et al [ 15 ] also report that acute phase reactants, such as C-reactive protein, could prove more accurate when establishing the association between cognitive impairment and inflammation, since clinical activity indexes are affected by subjective parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our evaluation of various inflammatory parameters, we found a stronger association between cognitive decline and C-reactive protein than with clinical activity indexes such as JADAS27. The activity index JADAS27 is the most used in JIA [ 25 , 37 ]. Shin et al [ 15 ] also report that acute phase reactants, such as C-reactive protein, could prove more accurate when establishing the association between cognitive impairment and inflammation, since clinical activity indexes are affected by subjective parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study [84] reported a positive association between adiposity and disease activity. According to the results, overweight/obesity in JIA correlated with the duration of biological therapy and PA levels, while the FMI of patients was associated with age, the 27-joint Juvenile Arthritis Disease Activity score (JADAS-27) and PA levels [84].…”
Section: Who Pcmentioning
confidence: 99%